Etch-and-rinse versus self-etch strategy of a universal adhesive in different application methods at the bonding interface of fiber post cementation - Barros, Antonia Patricia Oliveira [UNESP]; de Melo Alencar, Cristiane; Zambon, Matheus [UNESP]; de Andrade, Marcelo Ferrarezi [UNESP]; Fernández, Eduardo; Kuga, Milton Carlos [UNESP] (Wiley, 2023)
Objective: To evaluate the effect of etch-and-rinse (ER) versus self-etch (SE) strategies of a universal adhesive applied with a manual brush (MB) or rotary brush (RB) on the bonding interface of fiber post cementation. Methods: Forty bovine incisor roots were prepared and divided into four groups according to the methods of application and strategy of universal adhesive use (MB-ER, RB-ER, MB-SE and RB-SE). After 6 months, specimens from different thirds of the post space were evaluated of push-out strength, analysis of adhesive failure patterns, and extent of tags. Results: The RB-ER and RB-SE groups showed the highest bond strength values in the cervical and middle thirds of the post space. Cohesive adhesive failure had the highest incidence in the different thirds of the post space in the ER strategy, regardless of the adhesive application method. The RB-ER group showed the highest tag extensions. Conclusions: The protocols of universal adhesive application with RB provided the greater bond strength, but only the ER strategy favored the formation of a greater extension of tags at the adhesive interface. Clinical Significance: The application of universal adhesive with RB into the post space increases the strength of the post-cemented fiber bond.
Keywords: adhesive; bond strength; cementation; failure; fiber post; protocols